Species diversity and phylogeny of the green macroalga Ulva (Ulvophyceae, Chlorophyta) in Singapore - Ng, Yu Fei; Huang, Danwei (Phytotaxa, 2024)
The green macroalgal genus Ulva (Ulvaceae, Ulvophyceae, Chlorophyta) is commonly found in coastal ecosystems and confers many important marine ecological services. Despite prior research interest and recent advancements in Ulva taxonomy, in many parts of the world, its species diversity remains unresolved due to a high degree of morphological variation and phenotypic plasticity. DNA barcoding and phylogenetic approaches can potentially assist in identifying Ulva species precisely. Here, we analysed chloroplast tufA, rbcL and nuclear ITS from 49 Ulva specimens from Singapore. Gross and microscopic morphological examinations were also performed to characterise the morphological range of each species. Our results confirm the presence of three Ulva species in Singapore, all of which are new local records: U. meridionalis, U. ohnoi, and U. tepida. Although 10 Ulva species have been historically recorded in Singapore, none of them were found in the present study, likely due to prior misidentification, limited seasonal sampling, or local extirpations. Ulva ohnoi shows high morphological variation with five morphotypes. This study demonstrates that molecular analyses combined with morphological examinations are useful for characterising Ulva diversity.